Motivation and Participation in Health Care Guarantee with Compliance Control in Elderly Hypertension - Kustin,; Firdaus, Ahlul; Maurida, Nurul (Blambangan Journal of Nursing and Health Sciences (BJNHS), 2024)
Introduction : Elderly is the final process of development which is characterized by decreased cardiovascular function which causes hypertension. Hypertension can be prevented if the elderly regularly adopt a healthy and correct lifestyle, but in reality there are still many cases of hypertension that continue to increase. This is related to the motivation of hypertension sufferers and health insurance participation with control adherence. Compliance in undergoing hypertension treatment is very important so that symptoms of hypertension can be controlled. This study aims to determine the relationship between motivation and health insurance participation with control adherence in elderly hypertension at the Ajung Health Center. Methods: The research design used is quantitative with a cross-sectional design using a measuring instrument questionnaire with simple random sampling technique. The number of samples taken were 90 hypertensive elderly. Data is processed using multiple logistic regression test techniques. Results: The results obtained showed that the p value was 0.444 and 0.173 0.05 or Ha was rejected that there was no relationship between motivation and control compliance in elderly hypertension at the Ajung Health Center. Conclution: Families are expected to provide motivation to the elderly with hypertension to be more motivated in managing their lifestyle and controlling blood pressure regularly to prevent complications of hypertension. Conclusion: There is no relationship between motivation and health care participation with control compliance in elderly hypertension at the Ajung Health Center